Metal catalyst-loaded single-walled carbon nanotube / fabric composite flexible electrode, preparation method and application
Through the dispersant-free single-wall carbon nanotube conductive ink preparation and inkjet printing technology, a single-wall carbon nanotube/fabric composite flexible electrode is formed with metal catalyst-loaded, solving the problem of insufficient flexibility and corrosion resistance of traditional electrodes, and realizing the High conductivity and catalytic activity, suitable for wearable biosensors.
Patent Information
- Application Number
- CN202411641713.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-01-10
AI Technical Summary
In the prior art, single-walled carbon nanotube/fabric composite flexible electrodes supported by metal catalysts have shortcomings in flexibility, corrosion resistance and portability, and the use of dispersants in traditional preparation methods leads to poor physical and chemical properties of the electrodes.
Using the single-wall carbon nanotube conductive ink preparation method without dispersant, metal catalyst is directly deposited on the surface of the fabric through technologies such as ultrasonic crushing and inkjet printing to form a single-wall carbon nanotube/fabric composite flexible electrode supported by the metal catalyst.
High conductivity, good flexibility and catalytic activity are achieved, production costs are reduced, and the electrode shows significant catalytic activity in the electrochemical catalytic oxidation reaction of glucose, uric acid and lactic acid, and is suitable for wearable biosensors.
Smart Images

Figure CN119287412A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrode materials and their preparation and application, and in particular relates to a single-walled carbon nanotube / fabric composite flexible electrode loaded with a metal catalyst, a preparation method and an application thereof. Background Art
[0002] Single-walled carbon nanotubes are a new type of quasi-one-dimensional carbon single-element material. Due to their unique microstructure, the mechanical, electrical, and chemical properties of single-walled carbon nanotubes are significantly different from those of ordinary carbon materials. In terms of mechanics, single-walled carbon nanotubes have an extremely high aspect ratio and a stable sp2 hybrid structure. Therefore, fibers prepared with single-walled carbon nanotubes as raw materials have excellent flexibility and toughness, and the Young's modulus can reach 1TPa. In terms of electricity, single-walled carbon nanotubes can be divided into semiconductor type and metallic type, among which metallic single-walled carbon nanotubes can withstand up to 10 9 A / cm 2 In terms of chemistry, single-walled carbon nanotubes do not react with acids, alkalis, and organic solvents at room temperature, have excellent corrosion resistance, and can withstand temperatures up to 350°C in air and up to 1000°C in inert gas.
[0003] Wearable biosensors are devices that can be worn on the surface of a living organism for a long time and are used to monitor the concentration of a substance in the body. Miniaturization, lightweight, and flexibility are the development trends of wearable biosensor research and development. Therefore, electrochemical systems with flexible electrodes have good application prospects in wearable biosensors. By utilizing the properties of single-walled carbon nanotubes and coating them on the surface of fabrics, good flexible electrodes can be obtained. By modifying the surface of flexible electrodes with metal catalysts, flexible electrodes with catalytic activity for biological substances can be obtained. At present, there are no reports on single-walled carbon nanotube / fabric composite flexible electrodes loaded with metal catalysts. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects existing in the prior art and provide a single-walled carbon nanotube / fabric composite flexible electrode loaded with a metal catalyst, a preparation method and an application thereof. In the preparation method of the present invention, no dispersant is required in the raw materials for preparing the single-walled carbon nanotube conductive ink. Since the dispersant is usually a substance with poor conductivity and chemical stability, the single-walled carbon nanotube conductive ink without a dispersant ensures that the coated electrode has ideal physical and chemical properties, and eliminates the interference of the dispersant in the process of electrodeposition modification of the metal catalyst, which is more conducive to the formation of a direct charge transfer channel between the metal catalyst and the single-walled carbon nanotube, ensuring that the single-walled carbon nanotube / fabric composite flexible electrode loaded with a metal catalyst has excellent conductive properties; the operation steps are simple and easy, and large-scale production can be achieved by using common equipment such as an ultrasonic crusher and a doctor coater; the patterning of the flexible conductive channel can be easily achieved by inkjet printing and screen printing, providing a reliable path for preparing more complex wearable sensor devices; the entire preparation process does not use highly toxic or highly oxidizing chemicals, and has the advantages of being environmentally friendly, safe and controllable. The single-walled carbon nanotube / fabric composite flexible electrode loaded with a metal catalyst of the present invention has good flexibility, catalytic activity, skin affinity and conductivity. By making the metal catalyst, single-walled carbon nanotubes and fabric into a composite material, the defects of traditional sensor electrodes such as poor flexibility, poor corrosion resistance and poor portability are overcome, laying a foundation for the further development of wearable biosensors.
[0005] One of the purposes of the present invention is to provide a method for preparing a single-walled carbon nanotube / fabric composite flexible electrode loaded with a metal catalyst, comprising the following steps:
[0006] S1: uniformly mixing single-walled carbon nanotubes and an organic solvent to obtain single-walled carbon nanotube conductive ink;
[0007] S2: Clean and dry the fabric, then apply the single-walled carbon nanotube conductive ink prepared in step S1 on the surface of the fabric and dry it to obtain a single-walled carbon nanotube / fabric composite flexible electrode;
[0008] S3: Using the single-walled carbon nanotube / fabric composite flexible electrode prepared in step S2 as a cathode and a platinum sheet as an anode, and then placing the cathode and anode in an electrolyte containing metal cations in a metal catalyst, and using an electrochemical oxidation-reduction method to deposit a layer of metal catalyst on the surface of the cathode to obtain a single-walled carbon nanotube / fabric composite flexible electrode loaded with a metal catalyst.
[0009] The preferred technical solution is that the specific operation of step S1 is: adding a certain amount of single-walled carbon nanotubes and an organic solvent into a container, then placing the container containing the single-walled carbon nanotubes and the organic solvent in a constant temperature water bath device, and using a probe-type ultrasonic crusher to ultrasonically disperse at a certain water bath temperature to mix the single-walled carbon nanotubes and the organic solvent evenly.
[0010] A further preferred technical solution is that in the step S1: the organic solvent used is one or more of 1-methyl-2-pyrrolidone, dimethylformamide, and toluene, the mass concentration of single-walled carbon nanotubes in the single-walled carbon nanotube conductive ink is 0.1-2 mg / mL, and the water bath temperature is controlled at 0-15°C.
[0011] Another preferred technical solution is that in step S2: the fabric is cleaned with anhydrous ethanol and deionized water in turn and dried, the fabric used is one of cotton, linen, and polyester fiber cloth, and the single-walled carbon nanotube conductive ink is coated on the surface of the fabric by one or more of spraying, spin coating, scraping, inkjet printing, and screen printing.
[0012] Another preferred technical solution is that the specific operation of step S3 is: using the single-walled carbon nanotube / fabric composite flexible electrode prepared in step S2 as a cathode and a platinum sheet as an anode, placing the two in an electrolyte containing metal cations in a metal catalyst and electrically connecting them to a DC power supply, using an acid or alkaline solution to adjust the pH value of the electrolyte to an appropriate value, turning on the DC power supply so that the metal cations in the electrolyte are reduced to metal elements on the cathode surface, and depositing to form a layer of the metal catalyst.
[0013] A further preferred technical solution is that in step S3: the metal cation contained in the electrolyte is one of silver ions, gold ions, copper ions, and platinum ions, the concentration of the metal cation in the electrolyte is 10 to 10000 μmol / L, the pH value of the electrolyte is 4 to 10, and the current density on the cathode when power is turned on is 0.1 to 10 mA / cm 2 The power-on time is 1 to 30 minutes.
[0014] The second purpose of the present invention is to provide a single-walled carbon nanotube / fabric composite flexible electrode loaded with a metal catalyst, wherein the single-walled carbon nanotube / fabric composite flexible electrode loaded with a metal catalyst is prepared by the above-mentioned preparation method.
[0015] The third purpose of the present invention is to propose an application of a single-walled carbon nanotube / fabric composite flexible electrode loaded with a metal catalyst, and to use the single-walled carbon nanotube / fabric composite flexible electrode loaded with a metal catalyst for the electrochemical catalytic oxidation reaction of glucose, uric acid, and lactic acid.
[0016] The advantages and beneficial effects of the present invention are:
[0017] 1. A method for preparing a single-walled carbon nanotube / fabric composite flexible electrode loaded with a metal catalyst of the present invention does not require the use of a dispersant in the raw materials for preparing the single-walled carbon nanotube conductive ink. Since the dispersant is usually a substance with poor conductivity and chemical stability, the single-walled carbon nanotube conductive ink without a dispersant ensures that the coated electrode has ideal physical and chemical properties, and eliminates the interference of the dispersant in the process of electrodeposition modification of the metal catalyst, which is more conducive to the formation of a direct charge transfer channel between the metal catalyst and the single-walled carbon nanotube, thereby ensuring that the single-walled carbon nanotube / fabric composite flexible electrode loaded with a metal catalyst has excellent conductive properties.
[0018] 2. The preparation method of the single-walled carbon nanotube / fabric composite flexible electrode loaded with a metal catalyst of the present invention has simple and easy operation steps, and large-scale production can be achieved by using common equipment such as an ultrasonic crusher and a doctor coater. The patterning of flexible conductive channels can be easily achieved by inkjet printing and screen printing, providing a reliable path for the preparation of more complex wearable sensor devices. The entire preparation process does not use highly toxic or highly oxidizing chemicals, and has the advantages of being environmentally friendly, safe and controllable.
[0019] 3. The single-walled carbon nanotube / fabric composite flexible electrode loaded with a metal catalyst of the present invention can use common fabrics in clothing as a substrate. Compared with pure carbon nanotube electrodes, it can significantly reduce production costs while ensuring conductivity and flexibility. In addition, it is easy to combine with existing clothing production processes to realize the intelligence and functionalization of clothing.
[0020] 4. The single-walled carbon nanotube / fabric composite flexible electrode loaded with a metal catalyst of the present invention has good flexibility, catalytic activity, skin affinity and conductivity. By making the metal catalyst, single-walled carbon nanotube and fabric into a composite material, the defects of the traditional sensor electrode such as poor flexibility, poor corrosion resistance and poor portability are overcome, laying the foundation for the further development of wearable biosensors.
[0021] 5. The single-walled carbon nanotube / fabric composite flexible electrode loaded with metal catalysts of the present invention can be modified with a variety of metal catalysts onto the surface of the flexible electrode by electrodeposition under appropriate reaction conditions. It has good catalytic activity for the electrocatalytic oxidation of biological substances such as glucose and can be used as an electrode for a biofuel cell or an electrochemical biosensor. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Schematic diagram of the structure of the copper-loaded single-walled carbon nanotube / cotton cloth composite flexible electrode prepared in Example 1;
[0023] Figure 2 This is a scanning electron microscope photograph of the single-walled carbon nanotube / cotton cloth composite flexible electrode prepared in step S2 of Example 1;
[0024] Figure 3 (a) is a photograph of the single-walled carbon nanotube / cotton cloth composite flexible electrode prepared in step S2 of Example 1;
[0025] Figure 3 (b) is a photograph of the copper-loaded single-walled carbon nanotube / cotton cloth composite flexible electrode prepared in step S3 of Example 1;
[0026] Figure 4 This is a scanning electron microscope photograph of the copper-loaded single-walled carbon nanotube / cotton cloth composite flexible electrode prepared in Example 1;
[0027] Figure 5 The current-time curve of the copper-loaded single-walled carbon nanotube / cotton composite flexible electrode prepared in Example 1 in an electrolyte containing 0.4 mol / L sodium hydroxide at a constant potential of 0.36 V when a glucose solution is added dropwise to the electrolyte;
[0028] Figure 6 Cyclic voltammetry curves of the blank single-walled carbon nanotube / cotton cloth flexible electrode in Comparative Example 1 and the copper-loaded single-walled carbon nanotube / cotton cloth composite flexible electrode prepared in Example 1 in an electrolyte containing 2 mmol / L glucose and 0.4 mol / L sodium hydroxide. DETAILED DESCRIPTION
[0029] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and embodiments. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention.
[0030] Example 1
[0031] The method of the present invention is used to prepare a copper-loaded single-walled carbon nanotube / cotton cloth composite flexible electrode, which includes the following steps:
[0032] S1: adding a certain amount of single-walled carbon nanotubes and 1-methyl-2-pyrrolidone into a container, then placing the container containing the single-walled carbon nanotubes and 1-methyl-2-pyrrolidone in a constant temperature water bath, and using a probe-type ultrasonic crusher to ultrasonically disperse the single-walled carbon nanotubes and 1-methyl-2-pyrrolidone at a water bath temperature of 0°C to uniformly mix the single-walled carbon nanotubes and 1-methyl-2-pyrrolidone to obtain a single-walled carbon nanotube conductive ink, wherein the mass concentration of the single-walled carbon nanotubes in the single-walled carbon nanotube conductive ink is 0.5 mg / mL;
[0033] S2: Clean the cotton cloth with anhydrous ethanol and deionized water in turn and dry it, then apply the single-walled carbon nanotube conductive ink prepared in step S1 on the surface of the cotton cloth with a doctor blade and dry it to obtain a single-walled carbon nanotube / cotton cloth composite flexible electrode;
[0034] S3: The single-walled carbon nanotube / cotton cloth composite flexible electrode prepared in step S2 is used as a cathode and a platinum sheet is used as an anode. The two are placed in an electrolyte containing copper chloride and electrically connected to a DC power supply. The molar concentration of copper chloride is 100 μmol / L. The pH of the electrolyte is adjusted to 7 using hydrochloric acid or sodium hydroxide solution. The DC power supply is turned on and the current density on the cathode is controlled to 5 mA / cm 2 The power supply was turned on for 1 min, so that the copper ions in the electrolyte were reduced to copper on the cathode surface and deposited to form a layer of copper catalyst. The DC power supply was turned off, the cathode was taken out and dried, and a copper-loaded single-walled carbon nanotube / cotton composite flexible electrode was obtained. The schematic diagram of the structure of the electrode is shown in the attached figure. Figure 1 .
[0035] Figure 2 This is a scanning electron microscope photograph of the single-walled carbon nanotube / cotton cloth composite flexible electrode prepared in step S2 in Example 1. It can be seen from the figure that the single-walled carbon nanotube coating is densely attached to the cotton cloth fiber surface.
[0036] Figure 3 (a) is a photograph of the single-walled carbon nanotube / cotton cloth composite flexible electrode prepared in step S2 of Example 1, Figure 3 (b) is a photograph of the copper-loaded single-walled carbon nanotube / cotton cloth composite flexible electrode prepared in step S3 of Example 1. It can be seen from the figure that after electrochemical redox deposition treatment, a layer of light gray substance appears on the surface of the black single-walled carbon nanotube / cotton cloth composite flexible electrode, indicating that a layer of metallic copper is deposited on its surface.
[0037] Figure 4 This is a scanning electron microscope photograph of the copper-loaded single-walled carbon nanotube / cotton cloth composite flexible electrode prepared in Example 1. From the figure, it can be seen that a large number of metallic copper particles are attached to the surface of the single-walled carbon nanotube coating, and the particle size range of the metallic copper particles is 50 to 200 nm.
[0038] Figure 5The current-time curve of the copper-loaded single-walled carbon nanotube / cotton composite flexible electrode prepared in Example 1 in an electrolyte containing 0.4 mol / L sodium hydroxide, at a constant potential of 0.36 V, during the process of adding glucose solution dropwise to the electrolyte. The specific test conditions are: the working electrode, the counter electrode, and the reference electrode are respectively the copper-loaded single-walled carbon nanotube / cotton composite flexible electrode (in the shape of a rectangle with a diameter of 3 mm×4 mm), a platinum sheet, and a saturated calomel electrode. The electrolyte is a 0.4 mol / L sodium hydroxide aqueous solution. Each time a glucose solution is added to the electrolyte, the glucose concentration in the electrolyte can be increased by 2 mmol / L. Figure 5 It can be seen that as the glucose concentration increases, the current value also increases significantly. Therefore, the glucose concentration in the solution can be detected by measuring the current value.
[0039] Example 2
[0040] The method of the present invention is used to prepare a platinum-loaded single-walled carbon nanotube / linen composite flexible electrode, which includes the following steps:
[0041] S1: adding a certain amount of single-walled carbon nanotubes and dimethylformamide into a container, then placing the container containing the single-walled carbon nanotubes and dimethylformamide in a constant temperature water bath, and using a probe-type ultrasonic crusher to ultrasonically disperse the single-walled carbon nanotubes and dimethylformamide at a water bath temperature of 8°C to uniformly mix the single-walled carbon nanotubes and dimethylformamide to obtain a single-walled carbon nanotube conductive ink, wherein the mass concentration of the single-walled carbon nanotubes in the single-walled carbon nanotube conductive ink is 1.0 mg / mL;
[0042] S2: Clean the linen cloth with anhydrous ethanol and deionized water in turn and dry them, then spray the single-walled carbon nanotube conductive ink prepared in step S1 on the surface of the linen cloth with a spray gun and dry it to obtain a single-walled carbon nanotube / linen cloth composite flexible electrode;
[0043] S3: The single-walled carbon nanotube / linen composite flexible electrode prepared in step S2 is used as a cathode and a platinum sheet is used as an anode. The two are placed in an electrolyte containing chloroplatinic acid and electrically connected to a DC power supply. The molar concentration of chloroplatinic acid is 50 μmol / L. The pH of the electrolyte is adjusted to 6.5 using hydrochloric acid or sodium hydroxide solution. The DC power supply is turned on and the current density on the cathode is controlled to 1 mA / cm 2 The power-on time is 5 minutes, so that the platinum ions in the electrolyte are reduced to platinum element on the cathode surface and deposited to form a layer of platinum element catalyst. The DC power supply is turned off, the cathode is taken out and dried to obtain a single-walled carbon nanotube / linen composite flexible electrode loaded with platinum.
[0044] Example 3
[0045] The method of the present invention is used to prepare a gold-loaded single-walled carbon nanotube / polyester fiber cloth composite flexible electrode, which includes the following steps:
[0046] S1: adding a certain amount of single-walled carbon nanotubes and toluene into a container, then placing the container containing the single-walled carbon nanotubes and toluene in a constant temperature water bath, and using a probe-type ultrasonic crusher to ultrasonically disperse the single-walled carbon nanotubes and toluene at a water bath temperature of 15° C. to uniformly mix the single-walled carbon nanotubes and toluene to obtain a single-walled carbon nanotube conductive ink, wherein the mass concentration of the single-walled carbon nanotubes in the single-walled carbon nanotube conductive ink is 2.0 mg / mL;
[0047] S2: Clean the polyester fiber cloth with anhydrous ethanol and deionized water in turn and dry it, spin-coat the single-walled carbon nanotube conductive ink prepared in step S1 on the surface of the polyester fiber cloth and dry it to obtain a single-walled carbon nanotube / polyester fiber cloth composite flexible electrode;
[0048] S3: The single-walled carbon nanotube / polyester fiber cloth composite flexible electrode prepared in step S2 is used as a cathode and a platinum sheet is used as an anode. The two are placed in an electrolyte containing chloroauric acid and electrically connected to a DC power supply. The molar concentration of chloroauric acid is 10 μmol / L. The pH of the electrolyte is adjusted to 4.0 using hydrochloric acid or sodium hydroxide solution. The DC power supply is turned on and the current density on the cathode is controlled to 0.1 mA / cm 2 The power-on time is 30 minutes, so that the gold ions in the electrolyte are reduced to gold element on the cathode surface and deposited to form a layer of gold element catalyst. The DC power supply is turned off, the cathode is taken out and dried to obtain a gold-loaded single-walled carbon nanotube / polyester fiber cloth composite flexible electrode.
[0049] Example 4
[0050] The method of the present invention is used to prepare a copper-loaded single-walled carbon nanotube / cotton cloth composite flexible electrode, which includes the following steps:
[0051] S1: adding a certain amount of single-walled carbon nanotubes and 1-methyl-2-pyrrolidone into a container, then placing the container containing the single-walled carbon nanotubes and 1-methyl-2-pyrrolidone in a constant temperature water bath, and using a probe-type ultrasonic crusher to ultrasonically disperse the single-walled carbon nanotubes and 1-methyl-2-pyrrolidone at a water bath temperature of 10° C. to uniformly mix the single-walled carbon nanotubes and 1-methyl-2-pyrrolidone to obtain a single-walled carbon nanotube conductive ink, wherein the mass concentration of the single-walled carbon nanotubes in the single-walled carbon nanotube conductive ink is 0.1 mg / mL;
[0052] S2: Clean the cotton cloth with anhydrous ethanol and deionized water in turn and dry it, then apply the single-walled carbon nanotube conductive ink prepared in step S1 on the surface of the cotton cloth with a doctor blade and dry it to obtain a single-walled carbon nanotube / cotton cloth composite flexible electrode;
[0053] S3: The single-walled carbon nanotube / cotton cloth composite flexible electrode prepared in step S2 is used as a cathode and a platinum sheet is used as an anode. The two are placed in an electrolyte containing copper chloride and electrically connected to a DC power supply. The molar concentration of copper chloride is 5000 μmol / L. The pH of the electrolyte is adjusted to 7 using hydrochloric acid or sodium hydroxide solution. The DC power supply is turned on and the current density on the cathode is controlled to 10 mA / cm 2 The power-on time is 20 minutes, so that the copper ions in the electrolyte are reduced to copper element on the cathode surface and deposited to form a layer of copper element catalyst. The DC power supply is turned off, the cathode is taken out and dried to obtain a copper-loaded single-walled carbon nanotube / cotton cloth composite flexible electrode.
[0054] Example 5
[0055] The method of the present invention is used to prepare a copper-loaded single-walled carbon nanotube / cotton cloth composite flexible electrode, which includes the following steps:
[0056] S1: adding a certain amount of single-walled carbon nanotubes and 1-methyl-2-pyrrolidone into a container, then placing the container containing the single-walled carbon nanotubes and 1-methyl-2-pyrrolidone in a constant temperature water bath, and using a probe-type ultrasonic crusher to ultrasonically disperse the single-walled carbon nanotubes and 1-methyl-2-pyrrolidone at a water bath temperature of 12° C. to uniformly mix the single-walled carbon nanotubes and 1-methyl-2-pyrrolidone to obtain a single-walled carbon nanotube conductive ink, wherein the mass concentration of the single-walled carbon nanotubes in the single-walled carbon nanotube conductive ink is 1.5 mg / mL;
[0057] S2: Clean the cotton cloth with anhydrous ethanol and deionized water in turn and dry it, then apply the single-walled carbon nanotube conductive ink prepared in step S1 on the surface of the cotton cloth with a doctor blade and dry it to obtain a single-walled carbon nanotube / cotton cloth composite flexible electrode;
[0058] S3: The single-walled carbon nanotube / cotton cloth composite flexible electrode prepared in step S2 is used as a cathode and a platinum sheet is used as an anode. The two are placed in an electrolyte containing copper chloride and electrically connected to a DC power supply. The molar concentration of copper chloride is 10000 μmol / L. The pH of the electrolyte is adjusted to 7 using hydrochloric acid or sodium hydroxide solution. The DC power supply is turned on and the current density on the cathode is controlled to 8 mA / cm 2 The power-on time is 25 minutes, so that the copper ions in the electrolyte are reduced to copper element on the cathode surface and deposited to form a layer of copper element catalyst. The DC power supply is turned off, the cathode is taken out and dried to obtain a copper-loaded single-walled carbon nanotube / cotton cloth composite flexible electrode.
[0059] Comparative Example 1
[0060] Referring to step S1 and step S2 in Example 1, a blank single-walled carbon nanotube / cotton cloth composite flexible electrode is prepared, including the following steps:
[0061] S1: adding a certain amount of single-walled carbon nanotubes and 1-methyl-2-pyrrolidone into a container, then placing the container containing the single-walled carbon nanotubes and 1-methyl-2-pyrrolidone in a constant temperature water bath, and using a probe-type ultrasonic crusher to ultrasonically disperse the single-walled carbon nanotubes and 1-methyl-2-pyrrolidone at a water bath temperature of 0°C to uniformly mix the single-walled carbon nanotubes and 1-methyl-2-pyrrolidone to obtain a single-walled carbon nanotube conductive ink, wherein the mass concentration of the single-walled carbon nanotubes in the single-walled carbon nanotube conductive ink is 0.5 mg / mL;
[0062] S2: Clean the cotton cloth with anhydrous ethanol and deionized water in turn and dry it, then use a doctor blade to apply the single-walled carbon nanotube conductive ink prepared in step S1 on the surface of the cotton cloth and dry it to obtain a blank single-walled carbon nanotube / cotton cloth composite flexible electrode.
[0063] Comparative Example 2
[0064] A blank single-walled carbon nanotube / linen composite flexible electrode was prepared by referring to steps S1 and S2 in Example 2.
[0065] Comparative Example 3
[0066] A blank single-walled carbon nanotube / polyester fiber cloth composite flexible electrode was prepared by referring to step S1 and step S2 in Example 3.
[0067] (i) The copper-loaded single-walled carbon nanotube / cotton composite flexible electrode prepared in Example 1 and the blank single-walled carbon nanotube / cotton composite flexible electrode prepared in Comparative Example 1 were tested for their catalytic activity in the glucose oxidation reaction:
[0068] Test conditions: The working electrode is the flexible electrode to be tested (rectangular with a diameter of 3mmx4mm), the counter electrode is a platinum electrode, the reference electrode is a saturated calomel electrode, the electrolyte is an aqueous solution containing 0.4mol / L sodium hydroxide and 2mmol / L glucose, the cyclic voltammetry scan rate is 10mA / s, and the test results are shown in the attached Figure 6 .
[0069] Figure 6 Cyclic voltammetry curves of the blank single-walled carbon nanotube / cotton cloth flexible electrode in Comparative Example 1 and the copper-loaded single-walled carbon nanotube / cotton cloth composite flexible electrode prepared in Example 1 in an electrolyte containing 2 mmol / L glucose and 0.4 mol / L sodium hydroxide. Figure 6It can be seen that the copper-loaded single-walled carbon nanotube / cotton cloth composite flexible electrode prepared in Example 1 has an obvious glucose oxidation peak at 0.37V, which indicates that the electrode has significant catalytic activity for the electrocatalytic oxidation of glucose; while no oxidation peak is observed in the cyclic voltage curve of the blank single-walled carbon nanotube / cotton cloth composite flexible electrode in Comparative Example 1, which indicates that the electrode has no obvious catalytic activity for the electrocatalytic oxidation of glucose.
[0070] The copper-loaded single-walled carbon nanotube / cotton cloth composite flexible electrodes prepared in Example 4 and Example 5 were respectively examined for their electrocatalytic oxidation activity towards glucose with reference to the contents of step (i). The test results showed that the copper-loaded single-walled carbon nanotube / cotton cloth composite flexible electrodes prepared in Example 4 and Example 5 had an obvious glucose oxidation peak at 0.37 V, indicating that the electrodes had significant catalytic activity towards the electrocatalytic oxidation of glucose.
[0071] (ii) Referring to step (i), the platinum-loaded single-walled carbon nanotube / linen composite flexible electrode prepared in Example 2 and the blank single-walled carbon nanotube / linen composite flexible electrode prepared in Comparative Example 2 were tested for their catalytic activity in the uric acid oxidation reaction.
[0072] Test conditions: The working electrode is the flexible electrode to be tested (rectangular with a diameter of 3 mm x 4 mm), the counter electrode is a platinum electrode, the reference electrode is a saturated calomel electrode, the electrolyte is a phosphate buffer containing 2 mmol / L uric acid, the concentration of the phosphate buffer is 0.1 mol / L, the pH value is 5.5, and the cyclic voltammetry scan rate is 10 mA / s.
[0073] The results show that the platinum-loaded single-walled carbon nanotube / linen composite flexible electrode prepared in Example 2 has an obvious uric acid oxidation peak at 0.4V, which indicates that the electrode has significant catalytic activity for the electrocatalytic oxidation of uric acid; while no oxidation peak was observed in the cyclic voltage curve of the blank single-walled carbon nanotube / linen composite flexible electrode in Comparative Example 2, which indicates that the electrode has no obvious catalytic activity for the electrocatalytic oxidation of uric acid.
[0074] (III) Referring to step (I), the gold-loaded single-walled carbon nanotube / polyester fiber cloth composite flexible electrode prepared in Example 3 and the blank single-walled carbon nanotube / polyester fiber cloth composite flexible electrode prepared in Comparative Example 3 were tested for their catalytic activity in lactic acid oxidation reaction.
[0075] Test conditions: the working electrode is the flexible electrode to be tested (rectangular with a diameter of 3 mm x 4 mm), the counter electrode is a platinum electrode, the reference electrode is a saturated calomel electrode, the electrolyte is a phosphate buffer containing 2 mmol / L lactic acid, the concentration of the phosphate buffer is 0.1 mol / L, the pH value is 7.5, and the cyclic voltammetry scan rate is 10 mA / s.
[0076] The results show that the gold-loaded single-walled carbon nanotube / polyester fiber cloth composite flexible electrode prepared in Example 3 has an obvious lactic acid oxidation peak at 0.55V, which indicates that the electrode has significant catalytic activity for the electrocatalytic oxidation of lactic acid; while no oxidation peak was observed in the cyclic voltage curve of the blank single-walled carbon nanotube / polyester fiber cloth composite flexible electrode in Comparative Example 3, which indicates that the electrode has no obvious catalytic activity for the electrocatalytic oxidation of lactic acid.
[0077] In summary, the catalytic activity results of the composite flexible electrodes in Examples 1 to 3 and Comparative Examples 1 to 3 for the electrochemical oxidation reactions of glucose, uric acid and lactic acid respectively confirm that the single-walled carbon nanotube / fabric composite flexible electrode loaded with metal catalyst prepared by the method of the present invention has significant catalytic activity for the electrochemical redox reactions of glucose, uric acid and lactic acid. The single-walled carbon nanotube / fabric composite flexible electrode loaded with metal catalyst prepared by the method of the present invention can be used as an electrode in the electrochemical concentration detection method of glucose, uric acid and lactic acid, thereby achieving the purpose of the invention.
[0078] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a single-walled carbon nanotube / fabric composite flexible electrode loaded with a metal catalyst, characterized in that: The steps are as follows: S1: uniformly mixing single-walled carbon nanotubes and an organic solvent to obtain single-walled carbon nanotube conductive ink; S2: Clean and dry the fabric, then apply the single-walled carbon nanotube conductive ink prepared in step S1 on the surface of the fabric and dry it to obtain a single-walled carbon nanotube / fabric composite flexible electrode; S3: Using the single-walled carbon nanotube / fabric composite flexible electrode prepared in step S2 as a cathode and a platinum sheet as an anode, and then placing the cathode and anode in an electrolyte containing metal cations in a metal catalyst, and using an electrochemical oxidation-reduction method to deposit a layer of metal catalyst on the surface of the cathode to obtain a single-walled carbon nanotube / fabric composite flexible electrode loaded with a metal catalyst.
2. The method for preparing the single-walled carbon nanotube / fabric composite flexible electrode loaded with metal catalyst according to claim 1, characterized in that: The specific operation of step S1 is: adding a certain amount of single-walled carbon nanotubes and an organic solvent into a container, then placing the container containing the single-walled carbon nanotubes and the organic solvent in a constant temperature water bath device, and using a probe-type ultrasonic crusher to ultrasonically disperse at a certain water bath temperature to mix the single-walled carbon nanotubes and the organic solvent evenly.
3. The method for preparing the single-walled carbon nanotube / fabric composite flexible electrode loaded with metal catalyst according to claim 2, characterized in that: In the step S1, the organic solvent used is one or more of 1-methyl-2-pyrrolidone, dimethylformamide, and toluene, the mass concentration of single-walled carbon nanotubes in the single-walled carbon nanotube conductive ink is 0.1-2 mg / mL, and the water bath temperature is controlled at 0-15°C.
4. The method for preparing the single-walled carbon nanotube / fabric composite flexible electrode loaded with metal catalyst according to claim 1, characterized in that: In the step S2, the fabric is cleaned with anhydrous ethanol and deionized water in turn and dried, the fabric used is one of cotton, linen, and polyester fiber cloth, and the single-walled carbon nanotube conductive ink is coated on the surface of the fabric by one or more of spraying, spin coating, scraping, inkjet printing, and screen printing.
5. The method for preparing the single-walled carbon nanotube / fabric composite flexible electrode loaded with metal catalyst according to claim 1, characterized in that: The specific operation of step S3 is: using the single-walled carbon nanotube / fabric composite flexible electrode prepared in step S2 as a cathode and a platinum sheet as an anode, placing the two in an electrolyte containing metal cations in a metal catalyst and electrically connecting them to a direct current power supply, using an acid or alkaline solution to adjust the pH value of the electrolyte to an appropriate value, turning on the direct current power supply so that the metal cations in the electrolyte are reduced to metal elements on the cathode surface, and a layer of the metal catalyst is deposited.
6. The method for preparing the single-walled carbon nanotube / fabric composite flexible electrode loaded with metal catalyst according to claim 5, characterized in that: In step S3, the metal cation contained in the electrolyte is one of silver ions, gold ions, copper ions, and platinum ions, the concentration of the metal cation in the electrolyte is 10 to 10000 μmol / L, the pH value of the electrolyte is 4 to 10, and the current density on the cathode when power is turned on is 0.1 to 10 mA / cm 2 The power-on time is 1 to 30 minutes.
7. A single-walled carbon nanotube / fabric composite flexible electrode loaded with a metal catalyst, characterized in that: The metal catalyst-loaded single-walled carbon nanotube / fabric composite flexible electrode is prepared by the preparation method described in any one of claims 1 to 6.
8. An application of the single-walled carbon nanotube / fabric composite flexible electrode loaded with metal catalyst as claimed in claim 7, characterized in that: The single-walled carbon nanotube / fabric composite flexible electrode loaded with a metal catalyst is used for the electrochemical catalytic oxidation reaction of glucose, uric acid and lactic acid.